UNVEILING THE INTERPLAY OF COMPETITIVE ADVANTAGE, MANAGEMENT ACCOUNTING INFORMATION SYSTEMS AND SME PERFORMANCE - Wuryaningsih, Wuryaningsih (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research uses the resource-based view theory to examine the influence of competitive advantage on SME performance. Furthermore, this research also examines the effect of management accounting information systems on SME performance. This study used a survey method with 129 SMEs in Malang City, Indonesia. Research data was analyzed using Warp PLS 8.0. The research results show a significant effect between competitive advantage and management accounting information systems on the performance of SMEs. In addition, management accounting information systems can moderate the relationship between competitive advantage and SME performance. These results imply that SMEs must create a competitive advantage over competitors, which will positively affect profits. In addition, implementing a management accounting information system will further strengthen the role of competitive advantage in improving performance for SMEs